Exponential bounds and tails for additive random recursive sequences - Ludger Rüschendorf; Eva-Maria Schopp (Discrete Mathematics & Theoretical Computer Science, 2007)
Exponential bounds and tail estimates are derived for additive random recursive sequences, which typically arise as functionals of recursive structures, of random trees or in recursive algorithms. In particular they arise as parameters of divide and conquer type algorithms. We derive tail bounds from estimates of the Laplace transforms and of the moment sequences. For the proof we use some classical exponential bounds and some variants of the induction method. The paper generalizes results of R"osler (% citeyearNP{Roesler:91}, % citeyearNP{Roesler:92}) and % citeN{Neininger:05} on subgaussian tails to more general classes of additive random recursive sequences. It also gives sufficient conditions for tail bounds of the form $exp(-a t^p)$ which are based on a characterization of citeN{Kasahara:78}.